(3TQM TQGFY GdESdGes - (3GdHQZGfj, GdbRhjfj, eMeO Jbj Hf eMeO, J (B1263(3g`s ((3Ydj GdSGhLHdGZjs)
(3ChdgG (B:s
(3bhdg GdaUd GdSGOS aj GdeQGHMI hGdehGVYI hGdJhdjIs
(3BNQgG (B:s
(3ajbHd bhd GdOdGd hGdSeSGQ aj bjeI GdeJGY eY Gdjejf habO GdHjfI(B... (3hGddg CYdes
(3JHUQI GdeDda (B:s
(3GdTgjQ HGdTgjO GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3, U(B182s
(3GdCYdGe(B: (3L(B6(3, U(B62s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis